Impact of Ultrasound- and Microwave-Assisted Extraction on Bioactive Compounds and Biological Activities of Jania rubens and Sargassum muticum - Kahina Hamamouche; Zoubida Elhadj; Latifa Khattabi; Wafa Zahnit; Brahim Djemoui; Omar Kharoubi; Walid Boussebaa; Mouhamed Bouderballa; Mohammed EL Moustapha Kallouche; Sabry M. Attia; Sheikh F. Ahmad; Maria Atanassova; et al. (Marine Drugs)
This study represents the first investigation into the ultrasonic and microwave extraction of bioactive metabolites from Jania rubens (J. rubens) (red seaweed) and Sargassum. muticum (S. muticum) (brown seaweed), with a focus on their biological activities. The research compares ultrasound-assisted extraction (UAE) with microwave-assisted extraction (MAE) utilizing a hydromethanolic solvent to evaluate their effects on these seaweeds’ bioactive compounds and biological activities. The assessment included a series of antioxidant essays: DPPH, ABTS, phenanthroline, and total antioxidant capacity, followed by enzyme inhibition activities: alpha-amylase and urease. Results revealed significant proportions of phenolic compounds, ranging from 48.31 ± 0.32 to 74.42 ± 0.80 μg GAE/mg, depending on the extraction method. The extracts demonstrated a high antioxidant activity, with IC50 values ranging from 26.58 ± 0.39 to 87.55 ± 0.69 μg/mL. Notably, the MAE extract of S. muticum showed a value of 48.11 ± 2.75 μg/mL for alpha-amylase inhibition, which is strictly superior to the reference acarbose with an IC50 equal to 3431.01 μg/mL. UPLC-ESI-MS/MS analysis identified 14 bioactive compounds. The proportion of riboflavin with MAE was 70.58% and 59.11% for J. rubens and S. muticum fractions, respectively. These findings underscore the critical influence of extraction technique selection on bioactive compounds’ yield and efficiency, highlighting the potential of algal biomass as a sustainable alternative in various applications.